Comparison of pollen grain morphological features of selected species of the genus Crataegus (Rosaceae) and their spontaneous hybrids. (26th April 2013) - Wrońska‐Pilarek, Dorota; Bocianowski, Jan; Jagodziński, Andrzej M.
Abstract : The aim of our study was to verify, on the basis of statistical analyses of nine quantitative morphological features of pollen grains, the hypothesis that pollen grains of three parental species of Crataegus ( C. laevigata, C. monogyna, C. rhipidophylla ) differed from the pollen of three spontaneous hybrids of these species ( C. × macrocarpa, C . × media, C. × subsphaericea ). Contrast analysis revealed that a majority of the pollen features of hybrid species were characterized by significantly higher mean values than those of parental species. Analysis of pollen shape classes indicated that the parental species clearly differed from each other in contrast with hybrids, which were characterized by a similar proportion of pollen in individual pollen shape classes. Statistical analyses showed that the pollen grains of two parental species, C. laevigata and C. monogyna, were most similar to one another. Pollen grains of typical C. rhipidophylla were similar to the pollen of hybrids and the mean values of almost all studied pollen features [P, E, Exp, Exp/P, Le, d, d/E (PAI)] of C. rhipidophylla var. rhipidophylla were intermediate between those of C. monogyna and C. rhipidophylla var. lindmanii . This corroborates Zieliński's conjecture that C. rhipidophylla is probably an old, conserved hybrid between C. monogyna and C. calycina (= C. lindmanii = C. rhipidophylla var. lindmanii ). According to the analysis of canonical variables, C. × macrocarpa and C. × media pollen grains were most similar. C. × subsphaericea and C. rhipidophylla var. rhipidophylla and C. rhipidophylla var . lindmanii formed another pair (group), and C. monogyna and C. laevigata constituted separate 'single species groups'. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 172, 555–571.